2023
DOI: 10.1002/fft2.241
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized magnetic covalent organic framework nanocomposites for high‐efficiency adsorption of ethyl carbamate from liquor

Abstract: Ethyl carbamate (EC) is a kind of genotoxic and carcinogenic substance and potentially harmful to human health. In this study, simple and effective removal of EC from liquor samples by using the magnetic mesoporous adsorbent (Fe3O4@COFs) was investigated. Gas chromatography and triple quadrupole tandem mass spectrometry (GC‐MS/MS) was used to monitor the whole of adsorption process. The results showed that the adsorbent has high efficiency and fast adsorption capacity. Under the optimized adsorption parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Furthermore, the O 1s spectrum (Figure 4d) was centered at 533.5 and 531.4 eV, indicating the presence of C-O and C=O, respectively. In addition, the peaks at 724.8 and 711.3 eV from the deconvolution can be assigned to the Fe in Fe 2p 1/2 and Fe 2p 3/2 , respectively, and the peaks at 732.0 and 716.8 eV belong to the satellite peaks of Fe [18]. These results indicated that the construction of MB-COFs-4 was successful.…”
Section: Xps Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the O 1s spectrum (Figure 4d) was centered at 533.5 and 531.4 eV, indicating the presence of C-O and C=O, respectively. In addition, the peaks at 724.8 and 711.3 eV from the deconvolution can be assigned to the Fe in Fe 2p 1/2 and Fe 2p 3/2 , respectively, and the peaks at 732.0 and 716.8 eV belong to the satellite peaks of Fe [18]. These results indicated that the construction of MB-COFs-4 was successful.…”
Section: Xps Analysismentioning
confidence: 72%
“…However, even after high-speed centrifugation, pure COFs are difficult to completely separate from the solution owing to their low density, resulting in a large mass loss of COFs and low extraction efficiency [17]. To solve this challenge and improve the functionality of COFs, magnetic COFs incorporating Fe-based magnetic cores have been gradually applied to the MSPE process, which eliminates the tedious centrifugation step and achieves the rapid and complete separation of COFs from the solution [18]. Nevertheless, most reported magnetic COFs are monolayer COFs, which interact with compounds mainly through weak interactions such as hydrogen bonding, hydrophobic interactions, π-π interactions, and van der Waals' forces, resulting in low resistance to interference and poor extraction selectivity and efficiency for some analytes [19].…”
Section: Introductionmentioning
confidence: 99%